O operador evolução - Andrade, Antonio Fernando Prado de (Semina: Ciências Agrárias, 1983)
In this work we intend to develop the Mathematical Formalism of Non-Relativistic Quantum Mechanics in terms of two Basics Operators: Evolution Operator, and Density Operator and some of its properties. This article has didatic purposes.